Nitrogen-doped carbon nanotube coated CoP / Co2P heterostructure electrocatalyst as well as preparation method and application thereof
The preparation of the CoP/Co2P heterostructure electrocatalyst coated with nitrogen-doped carbon nanotubes has been solved, and the existing catalysts are corroded and agglomerated under acid and alkali conditions is achieved, achieving efficient and stable catalytic effect of electrolyzed water hydrogen production.
Patent Information
- Application Number
- CN202411734306.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The existing electrolytic hydrogen production catalysts have problems such as high cost, low stability and insufficient catalytic activity of noble metal-based catalysts, especially in the case of corrosion under acid and alkaline conditions, and there is agglomeration of transition metal phosphides in preparation and use.
A nitrogen-doped carbon nanotube is used to coat the CoP/Co2P heterostructure electrocatalyst. By cobalt nitrate hexahydrate and guanine as cobalt and carbon sources, the catalyst with a multi-stage pore structure and high specific surface area is prepared after high-temperature carbonization, calcination and phosphating treatment.
The catalyst showed good bifunctional activity and stability in hydrogen evolution reaction and oxygen evolution reaction, low overpotential, small Tafel slope, and high electrocatalytic activity in alkaline media. The stability test showed that the catalytic activity had only slightly attenuated within 72 hours.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst and a preparation method and application thereof. Background Art
[0002] Among clean energy sources, hydrogen has attracted widespread attention due to its high combustion energy and carbon-free characteristics. Among most hydrogen production methods, the method of producing hydrogen by electrolysis of water is the cleanest and pollution-free. Water electrolysis consists of two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Improving its operating efficiency requires efficient catalysts for catalysis, so it is necessary to develop new catalysts with long-term stability and high catalytic activity. At present, the most efficient water electrolysis is the precious metal catalyst platinum and ruthenium-based catalysts. However, precious metal catalysts are difficult to use on a large scale due to their small stock, high cost, poor stability and other problems. Therefore, many scientists are committed to developing alternatives to precious metal-based catalysts with high activity, strong stability and low cost.
[0003] At present, transition metal-based catalysts such as carbides, nitrides, sulfides, phosphides, etc. have been widely studied, especially transition metal phosphides (TMPs) such as molybdenum phosphide (MoP), iron phosphide (FeP), nickel phosphide (NiP), cobalt phosphide (CoP), etc., especially cobalt phosphide (CoP) is one of the excellent substitutes for precious metal-based catalysts. The high electronegativity of phosphorus (P) atoms in CoP is considered to be a proton receptor, which can attract electrons in the metal, thereby accelerating electron transfer and enhancing the electrocatalytic activity of the catalyst. However, TMPs are prone to agglomeration during preparation and are extremely easy to corrode under acidic and alkaline conditions. They still have unsatisfactory catalytic activity and stability. It is a good way to make transition metal phosphides (TMPs) into heterostructures with strong coupling effects, thereby increasing their active sites. Carbon materials have attracted extensive attention due to their large specific surface area, good electrical conductivity, and strong acid and alkali resistance. They can not only improve electrical conductivity, but also prevent metal agglomeration and enhance the dispersion of active sites. In particular, carbon nanotubes (CNTs) have been used to construct interface-rich heterojunction carrier materials due to their unique hollow nanostructure, large surface area, good electrical conductivity, and strong chemical stability. For example, patent publication number CN 109746008 A discloses a nitrogen-doped porous carbon nanotube water electrolysis catalyst embedded with CoP nanoparticles and a preparation method thereof. The prepared carbon nanotubes have a high specific surface area, high activity and stability, and improve the catalytic performance of water electrolysis.
[0004] Although traditional activated carbon materials have a high specific surface area, their pore size is mainly distributed within the range of micropores, which is not conducive to ion transfer and material transport. Biomass and biomolecules such as guanine are widely present in nature. The heteroatoms such as N that they possess will be doped into the carbon skeleton at high temperature. Due to the difference in atomic electronegativity, N doping can change the local charge distribution of the carbon skeleton; it can enhance the ability of carbon materials to combine with other components, increase the carrier concentration, and further enhance the conductivity of carbon materials. It has been widely used in heterogeneous structure carrier materials. For example, patent publication number CN118676385 A discloses a cobalt-nitrogen co-doped porous carbon material and its preparation and application. The method mainly uses guanine as a carbon source and a nitrogen source. Guanine has a rich nitrogen content, which can increase the nitrogen content of the material and increase the effective reaction active sites of the catalyst. The cobalt-nitrogen co-doped porous carbon material obtained by this method has a large specific surface area, a high nitrogen content and rich reaction active sites, and has a catalytic activity for oxygen reduction reaction that is far superior to commercial precious metal catalysts. The document "Self-Reconstruction of Co / Co2P Heterojunctions Confined in N-Doped CarbonNanotubes for Zinc–Air Flow Batteries" discloses a heterojunction Co / Co2P nanocrystal embedded in bamboo-like N-doped carbon nanotubes (Co / Co2P@NCNTs), which uses melamine as the nitrogen source and carbon source for the growth of nitrogen-doped carbon nanotubes (NCNTs), and triphenylphosphine provides the phosphorus source for the synthesis of the M2P phase. After heat treatment, Co / Co2P@NCNTs are obtained. The composite material has outstanding bifunctional ORR / OER activity and durability. However, the method of using melamine as a carbon source to prepare carbon materials has some significant disadvantages. The pore structure of the carbon material formed by melamine during the carbonization process is often not ideal, and it is difficult to achieve precise control of its pore structure through a simple process. Although melamine has a high nitrogen content, the degree of nitrogen doping during the preparation process may be affected by many factors, such as carbonization temperature, catalyst type, etc. The unevenness of nitrogen doping may affect the electrochemical properties of the carbon material. In addition, melamine itself is a toxic compound, and improper handling may have an impact on human health and the environment. Summary of the invention
[0005] In view of the above problems, the present invention provides a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst and its preparation method and application, wherein hexahydrated cobalt nitrate is used as a cobalt source and guanine is used as a carbon source, and after high-temperature carbonization, calcination and phosphating treatment, a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst is obtained. The catalyst has a large specific surface area, a pore size distribution showing a micropore-mesopore-macroporous multi-level pore structure distribution, multiple active sites, and high catalytic reaction efficiency.
[0006] The present invention is achieved through the following technical solutions:
[0007] A nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst is disclosed. The invention uses cobalt nitrate hexahydrate as a cobalt source and guanine as a carbon source. A cobalt precursor is synthesized by a high-temperature carbonization method. The cobalt precursor is then calcined to obtain a cobalt tetroxide precursor. The cobalt tetroxide precursor is phosphated to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst.
[0008] Furthermore, the specific surface area of the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst is 20 to 21 m 2 / g, the pore size distribution shows a multi-level pore structure of micropores, mesopores and macropores, and the pore structure is mainly distributed in the range of 3 to 4 nm.
[0009] A method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst as described above comprises the following steps:
[0010] (1) Preparation of cobalt precursor: guanine and cobalt nitrate hexahydrate are added to water, stirred in a constant temperature oil bath until dry, and after being fully ground, the resulting mixture powder is transferred to a tube furnace and calcined at high temperature in an inert gas atmosphere to obtain a cobalt precursor;
[0011] (2) Preparation of cobalt trioxide precursor: After the cobalt precursor in step (1) is fully ground, the obtained cobalt precursor powder is moved to a tube furnace and calcined in an air atmosphere to obtain a cobalt trioxide precursor;
[0012] (3) Phosphation treatment: The cobalt oxide precursor in step (2) is moved to the downstream of the tube furnace, and the sodium hypophosphite is moved to the upstream of the tube furnace, and phosphation treatment is performed under an inert gas atmosphere to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst.
[0013] Furthermore, in step (1), the mass ratio of guanine to cobalt nitrate hexahydrate is 1:0.3-0.5.
[0014] Furthermore, in step (1), the stirring temperature in the constant temperature oil bath is 60 to 70° C., and the stirring time is 18 to 24 hours.
[0015] Furthermore, in step (1), the high temperature calcination is carried out under an argon atmosphere at 700-800° C. for 1.5-2 h, with a heating rate of 3-5° C. / min and an argon gas flow rate of 120-150 mL / min.
[0016] Furthermore, in step (2), the calcination treatment is carried out in an air atmosphere at 320-380° C. for 1.5-2 h, with a heating rate of 2-3° C. / min.
[0017] Furthermore, in step (3), the mass ratio of the cobalt tetroxide precursor to sodium hypophosphite is 1:12-18.
[0018] Furthermore, in step (3), the phosphating treatment is carried out under an argon atmosphere at 300-400° C. for 1.5-2 h, with a heating rate of 2-3° C. / min and an argon gas flow rate of 120-150 mL / min.
[0019] An application of the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst as described above in hydrogen evolution reaction and oxygen evolution reaction.
[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0021] 1. The present invention uses hexahydrated cobalt nitrate as a cobalt source and biological molecule guanine as a carbon source and a nitrogen source, and adopts a high-temperature carbonization method to synthesize a cobalt precursor, and then calcines the cobalt precursor to obtain a cobalt tetraoxide precursor. After phosphating the cobalt tetraoxide precursor, a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst is obtained. The specific surface area of the catalyst is 20 to 21 m 2 / g, the pore size distribution is characterized by a micropore-mesopore-macroporous multi-level pore structure distribution, and the pore structure is mainly distributed in 3-4nm. The catalyst has a large specific surface area, many exposed active sites, and the heterogeneous structure has the phenomenon of electron transfer to the carbon carrier, which will adjust the electronic structure of the catalyst surface, improve the catalytic reaction efficiency, and show good bifunctional activity and strong stability in hydrogen evolution reaction and oxygen evolution reaction.
[0022] 2. The present invention uses the biological molecule guanine as a carbon source and a nitrogen source. Guanine has a relatively low HOMO energy level and multiple hydrogen bonds, and can self-assemble at high temperatures to form a single structure and expand into a more extensive planar network structure, thereby forming a multi-level pore structure distribution, increasing the specific surface area of the carbon material; and the nitrogen element itself is doped into the carbon nanotubes during the high-temperature carbonization process. The heteroatom doping into the carbon material will affect the charge redistribution of the carbon substrate. The graphite N, pyridine N and pyrrole N produced by high-temperature pyrolysis will improve the conductivity and stability of the carbon skeleton, thereby improving the catalytic efficiency of the catalyst.
[0023] 3. The Co metal ions of the present invention are reduced to metal Co by carbon under high-temperature calcination, and the metal cobalt nanoparticles are uniformly embedded in the carbon nanotube skeleton, which supports the formation of carbon nanotubes and provides anchoring points for the subsequent formation of heterojunction structures. The presence of carbon nanotubes prevents the metal from agglomerating easily at high temperatures, thereby exposing more active sites.
[0024] 4. The present invention is based on the engineering of constructing a heterostructure with rich interfaces. The metal cobalt embedded in the nitrogen-doped carbon nanotubes can be used as the anchoring point of the heterojunction and the carbon carrier through a one-step thermal decomposition, thereby providing abundant active sites and accelerating conductivity. The subsequent calcination in an air atmosphere oxidizes the metal Co to Co3O4. Annealing in air is conducive to exposing abundant active sites, thereby improving the electrocatalytic activity. Subsequently, a controllable phosphating method is used to prepare the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure. This post-phosphating method effectively prevents the agglomeration of the heterostructure.
[0025] 5. The present invention improves the catalytic activity through the interface effect between the heterostructure and the nitrogen-doped carbon nanotubes. First, the synthesized carbon nanotubes have the characteristics of a hollow nanostructure, a large specific surface area and a multi-level pore distribution, which provide channels for the transmission of ions. The structure of the carbon nanotubes can still remain unchanged after calcination and phosphating, indicating that the synthesized carbon nanotubes are stable and prevent corrosion in acidic and alkaline media and then structural changes. In addition, there is a strong electronic interaction between the synthesized heterostructure and the carbon nanotubes, which will enhance the intrinsic activity of the catalyst, thereby improving the catalytic activity of the catalyst in the catalytic reaction.
[0026] 6. The preparation method of the composite electrocatalyst of the present invention is simple to operate, the raw materials are readily available, the conditions are simple and mild, and the production cost is low. The composite electrocatalyst obtained by the present invention has high electrocatalytic activity in alkaline medium and can be applied to hydrogen evolution reaction and oxygen evolution reaction in alkaline medium. 2 The overpotentials under are 96mV and 311mV respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the preparation process of CoP / Co2P@NGNTs in Example 1.
[0028] Figure 2 XRD diagrams of CoP / Co2P@NGNTs prepared in Example 1 and Co@NGNTs, Co3O4@NGNTs, NGC, NGNTs, and CoP / Co2P prepared in Comparative Examples 1-5, respectively.
[0029] Figure 3 SEM images of CoP / Co2P@NGNTs prepared in Example 1 and Co@NGNTs, Co3O4@NGNTs, NGC, and NGNTs prepared in Comparative Examples 1-4, respectively.
[0030] Figure 4 This is the TEM image of CoP / Co2P@NGNTs prepared in Example 1.
[0031] Figure 5 This is the EDX element distribution diagram of CoP / Co2P@NGNTs prepared in Example 1.
[0032] Figure 6 N2 adsorption-desorption isotherms and pore size distribution curves of CoP / Co2P@NGNTs prepared in Example 1 and NGC and NGNTs prepared in Comparative Examples 3-4, respectively.
[0033] Figure 7 Raman spectra of CoP / Co2P@NGNTs prepared in Example 1 and NGC and NGNTs prepared in Comparative Examples 3-4, respectively.
[0034] Figure 8 XPS graphs of CoP / Co2P@NGNTs prepared in Example 1 and NGNTs and CoP / Co2P prepared in Comparative Examples 4-5, respectively.
[0035] Fig. 9 The electrocatalytic performance diagram of CoP / Co2P@NGNTs in Application Example 1 and Co@NGNTs, Co3O4@NGNTs, NGC, NGNTs, and CoP / Co2P in Comparative Examples 1-5 for HER and OER in alkaline media.
[0036] Fig.10 Chronoamperometric curves of CoP / Co2P@NGNTs for HER and OER in Application Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0038] Example 1
[0039] Preparation of Nitrogen-doped Carbon Nanotube-coated CoP / Co2P Heterostructure Electrocatalysts:
[0040] (1) Preparation of cobalt precursor: 3 g of guanine, 1.2 g of cobalt nitrate hexahydrate and 30 mL of water were added to a beaker and magnetically stirred in a constant temperature oil bath at 65 °C for 24 h to evaporate the water. The powder was then thoroughly ground into powder using a mortar and placed in a porcelain boat. The powder was then transferred to a tube furnace and kept at 800 °C for 2 h under an argon atmosphere at a heating rate of 5 °C / min and an argon gas flow rate of 150 mL / min to obtain a nitrogen-doped carbon nanotube-coated metal Co precursor (denoted as Co@NGNTs).
[0041] (2) Preparation of cobalt tetroxide precursor: After Co@NGNTs were thoroughly ground, they were placed in a porcelain boat and moved to a tube furnace. The mixture was heated at 350 °C for 2 h in an air atmosphere at a heating rate of 3 °C / min to obtain a nitrogen-doped carbon nanotube-coated metal Co3O4 precursor (denoted as Co3O4@NGNTs).
[0042] (3) Phosphating treatment: The Co3O4@NGNTs annealed in air were placed in a porcelain boat and moved to the downstream of the tube furnace. Sodium hypophosphite was placed in a porcelain boat and moved to the upstream of the tube furnace. The mass ratio of Co3O4@NGNTs to sodium hypophosphite was 1:15. The mixture was heated at 350°C for 2 h in an argon atmosphere with a heating rate of 3°C / min and an argon gas flow rate of 150 mL / min to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure (denoted as CoP / Co2P@NGNTs). The schematic diagram of the preparation process is shown in the figure. Figure 1 shown.
[0043] Example 2
[0044] Preparation of Nitrogen-doped Carbon Nanotube-coated CoP / Co2P Heterostructure Electrocatalysts:
[0045] (1) Preparation of cobalt precursor: 3 g of guanine, 1.0 g of cobalt nitrate hexahydrate and 30 mL of water were added to a beaker and magnetically stirred in a constant temperature oil bath at 60 °C for 20 h to evaporate the water. The mixture was then ground into powder using a mortar and placed in a porcelain boat. The powder was then transferred to a tube furnace and kept at 700 °C for 1.5 h under an argon atmosphere at a heating rate of 3 °C / min and an argon gas flow rate of 120 mL / min to obtain a nitrogen-doped carbon nanotube-coated metal Co precursor (denoted as Co@NGNTs).
[0046] (2) Preparation of cobalt tetroxide precursor: After Co@NGNTs were thoroughly ground, they were placed in a porcelain boat and moved to a tube furnace. The mixture was kept at 320 °C for 1.5 h in an air atmosphere at a heating rate of 2 °C / min to obtain a nitrogen-doped carbon nanotube-coated metal Co3O4 precursor (denoted as Co3O4@NGNTs).
[0047] (3) Phosphating treatment: The Co3O4@NGNTs annealed in air were placed in a porcelain boat and moved to the downstream of the tube furnace. Sodium hypophosphite was placed in a porcelain boat and moved to the upstream of the tube furnace. The mass ratio of Co3O4@NGNTs to sodium hypophosphite was 1:12. The mixture was heated at 300°C for 1.5 h in an argon atmosphere with a heating rate of 2°C / min and an argon gas flow rate of 120 mL / min to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure (denoted as CoP / Co2P@NGNTs).
[0048] Example 3
[0049] Preparation of Nitrogen-doped Carbon Nanotube-coated CoP / Co2P Heterostructure Electrocatalysts:
[0050] (1) Preparation of cobalt precursor: 3 g of guanine, 1.5 g of cobalt nitrate hexahydrate and 30 mL of water were added to a beaker and magnetically stirred in a constant temperature oil bath at 70 °C for 18 h to evaporate the water. The mixture was then ground into powder using a mortar and placed in a porcelain boat. The powder was then transferred to a tube furnace and kept at 750 °C for 2 h under an argon atmosphere at a heating rate of 5 °C / min and an argon gas flow rate of 150 mL / min to obtain a nitrogen-doped carbon nanotube-coated metal Co precursor (denoted as Co@NGNTs).
[0051] (2) Preparation of cobalt tetroxide precursor: After Co@NGNTs were thoroughly ground, they were placed in a porcelain boat and moved to a tube furnace. The mixture was kept at 380°C for 1.5 h in an air atmosphere at a heating rate of 3°C / min to obtain a nitrogen-doped carbon nanotube-coated metal Co3O4 precursor (denoted as Co3O4@NGNTs).
[0052] (3) Phosphating treatment: The Co3O4@NGNTs annealed in air were placed in a porcelain boat and moved to the downstream of the tube furnace. Sodium hypophosphite was placed in a porcelain boat and moved to the upstream of the tube furnace. The mass ratio of Co3O4@NGNTs to sodium hypophosphite was 1:18. The mixture was heated at 400°C for 1.4 h in an argon atmosphere with a heating rate of 3°C / min and an argon gas flow rate of 150 mL / min to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure (denoted as CoP / Co2P@NGNTs).
[0053] Comparative Example 1
[0054] Comparative Example 1 is the Co@NGNTs in Example 1.
[0055] Comparative Example 2
[0056] Comparative Example 2 is the Co3O4@NGNTs in Example 1.
[0057] Comparative Example 3
[0058] The preparation method of Co@NGNTs in Comparative Example 3 is the same as that in Example 1. In the preparation process of Comparative Example 3, cobalt nitrate hexahydrate is not added to obtain a carbon material without adding metal (denoted as NGC).
[0059] Comparative Example 4
[0060] 0.3 g of Co@NGNTs in Example 1 was added to 250 mL of 1 mol / L HCl, stirred at room temperature for 24 h, then rinsed with ethanol and water for multiple times, and freeze-dried to obtain acid-washed carbon nanotubes (referred to as NGNTs).
[0061] Comparative Example 5
[0062] The Co@NGNTs in Example 1 were placed in a porcelain boat, moved to a tubular furnace, and kept at 600°C for 4 hours in an air atmosphere. The carbon was oxidized in the air to obtain pure Co3O4 (denoted as Co3O4). Subsequently, the Co3O4 annealed in the air was placed in a porcelain boat and moved to the downstream of the tubular furnace. Sodium hypophosphite was placed in a porcelain boat and moved to the upstream of the tubular furnace. The mass ratio of Co3O4 to sodium hypophosphite was 1:30. The mixture was kept at 350°C for 2 hours in an argon atmosphere. The heating rate was 3°C / min, and the argon gas flow rate was 150 mL / min. A CoP / Co2P heterostructure (denoted as CoP / Co2P) was obtained.
[0063] Material Characterization Analysis
[0064] (I) X-ray diffraction (XRD) analysis
[0065] In order to analyze the crystal phase of the synthesized catalyst, different catalysts were studied using X-ray diffractometer (XRD). Figure 2 shown. Figure 2 (a) is the XRD pattern of Co@NGNTs prepared in comparative example 1, Figure 2 (b) is the XRD pattern of Co3O4@NGNTs prepared in Comparative Example 2 and Co3O4 prepared in Comparative Example 5, Figure 2 (c) is the XRD pattern of NGC prepared in Comparative Example 3 and NGNTs prepared in Comparative Example 4, Figure 2 (d) is the XRD pattern of CoP / Co2P@NGNTs prepared in Example 1 and CoP / Co2P prepared in Comparative Example 5.
[0066] from Figure 2(a) It can be seen that the Co@NGNTs catalyst synthesized in Comparative Example 1 has diffraction peaks at 2θ=44.7°, 51.8°, 75.8°, etc., which correspond to the (111), (200) and (220) crystal planes of metal Co (PDF#41-1487), respectively. This is because carbon has a reducing property at high temperature to convert Co 2+ Reduced to metallic Co, and has a broad diffraction peak at 26.3°, corresponding to the (002) crystal plane of graphitic carbon (PDF#41-1487). Figure 2 (b) It can be seen that the Co3O4@NGNTs prepared in Comparative Example 2 and the pure Co3O4 prepared in Comparative Example 5 correspond well to the Co3O4 standard card (PDF#73-1701). The only difference between the two is that pure Co3O4 does not have the characteristic peak of graphite carbon of carbon materials, which indicates that the carbon is oxidized after calcination at 600℃. Figure 2 (c) It can be seen that the XRD spectra of NGC prepared in Comparative Example 3 and NGNTs prepared in Comparative Example 4 both show characteristic peaks of carbon materials, but the 44.7°(111), 51.8°(200) and 75.8°(220) in the XRD spectrum of NGNTs belong to the metal Co (PDF#15-0806) present. This is because the metal wrapped in the carbon cannot come into contact with hydrochloric acid and thus cannot be washed away. Figure 2 (d) It can be seen that in the XRD spectra of CoP / Co2P@NGNTs prepared in Example 1 and CoP / Co2P prepared in Comparative Example 5, the peaks centered at 31.6°, 36.3°, 46.2°, 48.1°, 56.0°, 61.7° and 78.0° correspond to the (011), (111), (112), (211), (020), (203) and (204) crystal planes of CoP, respectively (PDF#29-0497), and the peaks centered at 40.7°, 42.0° and 44.1° correspond to the (121), (220) and (130) planes of Co2P, respectively (PDF#32-0306), and CoP / Co2P does not have the characteristic peaks of graphite carbon. The above analysis proves the successful synthesis of the catalyst.
[0067] (ii) Scanning electron microscopy (SEM) analysis
[0068] The CoP / Co2P@NGNTs prepared in Example 1 and the Co@NGNTs, Co3O4@NGNTs, NGC, and NGNTs prepared in Comparative Examples 1-4 were characterized and analyzed using a scanning electron microscope (SEM). The characterization results are shown in FIG. Figure 3 shown. Figure 3(ae) SEM images of Co@NGNTs, Co3O4@NGNTs, CoP / Co2P@NGNTs, NGC, and NGNTs, respectively.
[0069] from Figure 3 (a) It can be seen that Co@NGNTs presents a bamboo-like carbon nanotube morphology, and the metal cobalt nanoparticles are evenly embedded in the carbon nanotube skeleton, providing more anchoring points for the combination of heterogeneous structures. Figure 3 (b) It can be seen that after Co3O4@NGNTs were calcined at 350℃, the metal Co was converted into Co3O4, and the carbon nanotube morphology was still maintained. Figure 3 (c) It can be seen that after the CoP / Co2P@NGNTs are phosphated, the CoP / Co2P heterostructure of nitrogen-doped carbon nanotubes is obtained, and it can be seen that the heterostructure nanoparticles are uniformly embedded in the carbon nanotubes. Figure 3 (d) It can be seen that the NGC after calcination without adding metal presents a nanosheet morphology, which fully demonstrates that the formation of carbon nanotubes is due to the support of metal Co. Figure 3 (e) It can be seen that for NGNTs, the SEM image of the synthesized Co-doped carbon nanotubes after being dissolved in 1 mol / L HCl shows that the carbon nanotubes are cross-linked into a network. It can be seen that the morphology after acid washing has basically not changed much, indicating that the synthesized carbon nanotubes have extremely strong stability. The highly stable carbon nanotubes can keep the morphology of the catalyst unchanged during the catalytic reaction, thereby having strong stability.
[0070] (III) Transmission electron microscopy (TEM) analysis
[0071] The CoP / Co2P@NGNTs prepared in Example 1 were characterized and analyzed using a transmission electron microscope (TEM). Figure 4 As shown, Figure 4 (ad) are TEM images of CoP / Co2P@NGNTs at different magnifications. Figure 4 It can be seen more clearly that nitrogen-doped carbon nanotubes are coated with CoP / Co2P heterostructures. The heterostructures were analyzed by HRTEM, and different lattice fringes formed by CoP (203), Co2P (121) and graphite (002) crystal planes were found on the carbon substrate. The stripe spacings are 0.1504, 0.2253 and 0.3368 nm, respectively, proving the formation of material heterostructures.
[0072] (IV) Energy dispersive X-ray (EDX) analysis
[0073] Energy dispersive X-ray spectroscopy (EDX) was used to characterize the CoP / Co2P@NGNTs prepared in Example 1. The characterization results are as follows: Figure 5 As shown. Figure 5 It can be seen that CoP / Co2P@NGNTs consists of C, N, O, Co and P, which are uniformly distributed in the composites.
[0074] (V) Specific surface area and pore size analysis
[0075] The specific surface area and pore size distribution of CoP / Co2P@NGNTs prepared in Example 1 and NGC and NGNTs prepared in Comparative Examples 3-4 were analyzed. The characterization results are as follows: Figure 6 shown. Figure 6 (a) is the N2 adsorption-desorption isotherm diagram, Figure 6 (b) is the pore size distribution curve.
[0076] Depend on Figure 6 (a) It can be seen that NGC, NGNTs and CoP / Co2P@NGNTs show obvious hysteresis curves in the medium and high pressure (0.5-1.0) region, which can be attributed to the fact that the synthesized catalysts show a hierarchical porous structure. CoP / Co2P@NGNTs (20.03m 2 / g) compared to NGC (24.72m 2 / g) is slightly reduced, which is caused by the loading of heterojunction nanoparticles. NGNTs has the largest specific surface area (349.19 m 2 / g), this is because the metal Co covers the pore structure on the carbon nanotubes. After acid washing, the metal Co is washed away, and the specific surface area has a large increase. Figure 6 In (b), the pore size distribution ( Figure 6 (b) Illustration) shows the characteristics of the micropore-mesopore-macroporous multi-level pore structure distribution. The pore structure is mainly distributed in 3-4nm. The large specific surface area and multi-level pore distribution characteristics can provide channels for the transfer of ions during the reaction and accelerate the catalytic reaction rate.
[0077] (VI) Raman spectroscopy analysis
[0078] Raman spectroscopy (Raman) was used to characterize the CoP / Co2P@NGNTs prepared in Example 1 and the NGC and NGNTs prepared in Comparative Examples 3-4, respectively. The characterization results are as follows: Figure 7 shown.
[0079] from Figure 7 It can be seen that the Raman spectrum of CoP / Co2P@NGNTs shows a -1 and 1586cm -1The characteristic D band and G band, which are associated with disordered carbon and graphitic carbon, respectively, are at 2680 cm -1 The characteristic broad 2D band at indicates the presence of graphite sheet structure in CoP / Co2P@NGNTs. The ID / IG ratio of CoP / Co2P@NGNTs is 0.88, which is smaller than 1.08 of NGC and 0.92 of NGNTs, indicating that the loading of CoP / Co2P heterostructure is conducive to the formation of graphite structure, thereby increasing the conductivity of carbon nanotubes and promoting electron transfer.
[0080] (VII) X-ray Photoelectron Spectroscopy (XPS) Analysis
[0081] The surface element composition and valence state of CoP / Co2P@NGNTs prepared in Example 1 and NGNTs and CoP / Co2P prepared in Comparative Examples 4-5 were measured by X-ray photoelectron spectroscopy (XPS). Figure 8 shown. Figure 8 (a) N1s spectra of CoP / Co2P@NGNTs and NGNTs. Figure 8 (b) P 2p spectra of CoP / Co2P@NGNTs and CoP / Co2P. Figure 8 (c) Co 2p spectra of CoP / Co2P@NGNTs and CoP / Co2P.
[0082] from Figure 8 (a) It can be seen that there are three forms of N in CoP / Co2P@NGNTs, including pyridinic N (398.68 eV), pyrrolic N (400.54 eV), and graphitic N (402.4 eV). Pyridinic N can improve the conductivity of the carbon skeleton, thereby promoting the transfer of electrons. Graphitic N groups can also serve as auxiliary active sites to accelerate the kinetics of catalytic reactions. Compared with NGNTs, pyridinic N in CoP / Co2P@NGNTs moved 0.83 eV to a lower binding energy, indicating that after loading the heterojunction, the electron cloud density of the carbon carrier increased, and there was a strong electronic interaction between the heterostructure and the carbon carrier.
[0083] from Figure 8 (b) It can be seen that CoP / Co2P@NGNTs has four different peaks at 135.25 eV, 133.94 eV, 130.82 eV and 129.78 eV, corresponding to PO, P 2p 1 / 2 and P 2p 2 / 3 After loading NGNTs, P 2p shifts positively, indicating that after loading carbon nanotubes, the electron cloud density of P decreases and electron transfer occurs. Based on the movement of pyridine nitrogen to high binding energy, Co-P and P 2p 3 / 2The movement toward lower binding energy indicates that there is a phenomenon of electron transfer from the heterostructure to the carbon support in CoP / Co2P@NGNTs, which will adjust the electronic structure of the catalyst surface and thus improve the catalytic efficiency in the catalytic reaction.
[0084] from Figure 8 (c) It can be seen that the two strong peaks of CoP / Co2P@NGNTs correspond to Co 2p 3 / 2 and Co 2p 1 / 2 The states at 798.45eV and 781.62eV can be attributed to Co 3+ , which means that Co exists in a positive trivalent form. The values at 798.42eV and 783.86eV can be attributed to the presence of Co on the catalyst surface. 2+ Compared with CoP / Co2P, the Co-P peak of CoP / Co2P@NGNTs has a negative shift of 1.3 eV, which indicates that the electron cloud density of Co decreases after loading carbon nanotubes, and electrons are lost, thereby inducing charge redistribution and transfer, and adjusting the electronic structure of the CoP / Co2P@NGNTs surface. Based on the movement of pyridinic nitrogen to high binding energy, Co-P and P 2p 3 / 2 The movement toward lower binding energy indicates that there is electron transfer from the heterostructure to the carbon support in CoP / Co2P@NGNTs, which will adjust the electronic structure of the catalyst surface and thus improve the catalytic efficiency in the catalytic reaction.
[0085] Application Example 1
[0086] 3 mg of CoP / Co2P@NGNTs prepared in Example 1 was placed in a 10 mL centrifuge tube, and 280 μL of ethanol, 140 μL of water, and 32 μL of nafion were added. After ultrasonic dispersion, 110 μL was evenly applied on a 1 cm*1 cm carbon paper, with a mass loading of 0.8 mg / cm 2 , and dried naturally at room temperature. All electrochemical tests were performed using Shanghai Chenhua (CHI 760E) and Bio-Logic SAS, using a typical three-electrode device, at room temperature in 1 mol / L KOH, using a saturated calomel electrode as the reference electrode (Hg / Hg2Cl2 saturated KCl), a graphite rod as the counter electrode, and carbon paper (CF) as the working electrode. The CoP / Co2P@NGNTs were tested for HER and OER at a current density of 10 mA cm -2 The overpotentials under are 96mV and 311mV respectively.
[0087] Application Comparative Example 1
[0088] The difference between Application Example 1 and Application Example 1 is that the catalyst used in Application Example 1 is Co@NGNTs in Application Example 1, and the other reaction conditions and test conditions are the same as those in Application Example 1. The test shows that Co@NGNTs has a significant effect on HER and OER at a current density of 10 mA·cm -2 The overpotentials under are 180mV and 376mV respectively.
[0089] Application Comparative Example 2
[0090] The difference between Application Example 2 and Application Example 1 is that the catalyst used in Application Example 2 is Co3O4@NGNTs in Application Example 2, and the other reaction conditions and test conditions are the same as those in Application Example 1. The test shows that Co3O4@NGNTs has a significant effect on HER and OER at a current density of 10 mA·cm -2 The overpotentials under are 245mV and 391mV respectively.
[0091] Application Comparative Example 3
[0092] The difference between Application Example 3 and Application Example 1 is that the catalyst used in Application Example 3 is NGC in Application Example 3, and the other reaction conditions and test conditions are the same as those in Application Example 1. The test shows that NGC has a significant effect on HER and OER at a current density of 10 mA cm -2 The overpotentials under are 412mV and 426mV respectively.
[0093] Application Comparative Example 4
[0094] The difference between Application Example 4 and Application Example 1 is that the catalyst used in Application Example 4 is NGNTs in Application Example 4, and the other reaction conditions and test conditions are the same as those in Application Example 1. -2 The overpotential is 419 mV.
[0095] Application Comparative Example 5
[0096] The difference between Application Example 5 and Application Example 1 is that the catalyst used in Application Example 5 is CoP / Co2P in Application Example 5, and the other reaction conditions and test conditions are the same as those in Application Example 1. The test shows that CoP / Co2P has a significant effect on HER and OER at a current density of 10 mA·cm -2 The overpotentials under are 162mV and 342mV respectively.
[0097] Analysis of electrocatalytic performance of materials
[0098] The performance of hydrogen evolution and oxygen evolution in alkaline medium of the catalysts of Comparative Examples 1-5 and Example 1 was analyzed. The analysis results are as follows: Fig. 9shown. Fig. 9 (a) and (b) are the HER LSV performance diagrams and Tafel slope diagrams of the samples in alkaline medium. It can be seen from the figures that CoP / Co2P@NGNTs, Co@NGNTs, Co3O4@NGNTs, NGC, CoP / Co2P have the highest HER performance at a current density of 10 mA cm -2 The overpotentials under the conditions are 96, 180, 245, 412, and 162 mV, respectively, and the corresponding Tafel slopes are 84, 158.8, 183.9, 437.6, and 113.7 mV·dec -1 NGNTs at 10 mA·cm -2 The lower overpotential has a relatively large specific surface area, so the double-layer capacitance is large, resulting in a relatively high test baseline, so 10mA·cm -2 The overpotential reading is inaccurate, and its Tafel slope is 299.1mV·dec -1 From the above test results, it can be seen that CoP / Co2P@NGNTs has the strongest electrocatalytic activity. -2 It has the smallest HER overpotential and the smallest Tafel slope.
[0099] Fig. 9 (c) and 9(d) are the OER LSV performance diagrams and Tafel slope diagrams of the samples in alkaline medium. It can be seen from the figures that CoP / Co2P@NGNTs, Co@NGNTs, Co3O4@NGNTs, NGC, NGNTs, CoP / Co2P have the highest OER performance at a current density of 10 mA cm -2 The overpotentials under the conditions are 311, 376, 391, 426, 419, and 342 mV, respectively, and the corresponding Tafel slopes are 76.4, 146.9, 127.7, 276.6, 160.7, and 119 mV·dec. -1 From the above test results, it can be seen that CoP / Co2P@NGNTs has the strongest electrocatalytic activity. -2 It has the smallest OER overpotential and the smallest Tafel slope.
[0100] Fig. 9 (e) is the Nyquist plot. It can be seen from the figure that CoP / Co2P@NGNTs has the smallest Nyquist semicircle diameter, which indicates that the charge transfer resistance is the lowest in the CoP / Co2P@NGNTs material and the charge transfer efficiency is fast. The CV graph is used to estimate the electrochemical double layer capacitance (C dl ) and draw the image, the result is as follows Fig. 9 (f) Fig. 9(f) is the current density versus scan rate diagram. In comparison, the ECSA area of CoP / Co2P@NGNTs is larger than that of other materials. dl The value is significantly higher than other materials, which is 56.1mF·cm -2 .
[0101] The stability of the CoP / Co2P@NGNTs catalyst for HER and OER was evaluated by chronoamperometric curves at 10 mA cm -2 The stability test was carried out for 72 hours under the conditions. The test results are as follows Fig.10 As shown, Fig.10 (a) is the chronoamperometric curve of HER. Fig.10 (b) is the chronoamperometric curve of OER. Fig.10 It can be seen that after 72 hours of stability test, there is only a slight decay, indicating that the CoP / Co2P@NGNTs catalyst has good stability for HER and OER.
[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst, characterized in that: Using cobalt nitrate hexahydrate as the cobalt source and guanine as the carbon source and nitrogen source, a cobalt precursor was synthesized by a high-temperature carbonization method, and then the cobalt precursor was calcined to obtain a cobalt tetroxide precursor. After the cobalt tetroxide precursor was phosphated, a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst was obtained.
2. The nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 1, characterized in that: The specific surface area of the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst is 20 to 21 m 2 / g, the pore size distribution shows a multi-level pore structure of micropores, mesopores and macropores, and the pore structure is mainly distributed in the range of 3 to 4 nm.
3. A method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of cobalt precursor: Guanine and cobalt nitrate hexahydrate are added to water, stirred in a constant temperature oil bath until dry, and after sufficient grinding, the resulting mixture powder is transferred to a tube furnace, calcined and carbonized at high temperature in an inert gas atmosphere to obtain a cobalt precursor; (2) Preparation of cobalt trioxide precursor: After the cobalt precursor in step (1) is fully ground, the obtained cobalt precursor powder is moved to a tube furnace and calcined in an air atmosphere to obtain a cobalt trioxide precursor; (3) Phosphation treatment: The cobalt oxide precursor in step (2) is moved to the downstream of the tube furnace, and the sodium hypophosphite is moved to the upstream of the tube furnace, and phosphation treatment is performed under an inert gas atmosphere to obtain a nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst.
4. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (1), the mass ratio of guanine to cobalt nitrate hexahydrate is 1:0.3-0.
5.
5. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (1), the stirring temperature in the constant temperature oil bath is 60 to 70° C., and the stirring time is 18 to 24 hours.
6. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (1), the high temperature calcination is carried out under an argon atmosphere at 700-800° C. for 1.5-2 h, with a heating rate of 3-5° C. / min and an argon gas flow rate of 120-150 mL / min.
7. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (2), the calcination treatment is carried out in an air atmosphere at 320-380° C. for 1.5-2 h, with a heating rate of 2-3° C. / min.
8. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (3), the mass ratio of the cobalt tetroxide precursor to sodium hypophosphite is 1:12-18.
9. The method for preparing the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst according to claim 3, characterized in that: In step (3), the phosphating treatment is carried out under an argon atmosphere at 300-400° C. for 1.5-2 h, with a heating rate of 2-3° C. / min and an argon gas flow rate of 120-150 mL / min.
10. Use of the nitrogen-doped carbon nanotube-coated CoP / Co2P heterostructure electrocatalyst as claimed in claim 1 or 2 in hydrogen evolution reaction and oxygen evolution reaction.
Citation Information
Patent Citations
CoP nano granule embedded nitrogen-doped porous carbon nanotube electrolysed water catalyst and preparation method thereof
CN109746008A
Cobalt-nitrogen co-doped porous carbon material and preparation and application thereof
CN118676385A
Cited By
Carbon nanotube in-situ packaged Fe-Co2P / CoP difunctional electrocatalyst and preparation method thereof
CN121023574A
Heterojunction catalyst with reconstructed surface as well as preparation method and application of heterojunction catalyst
CN121161356A